Overview of the ²⁰Ne + ⁷⁶Ge reaction mechanisms at E_lab= 275 MeV - Pappalardo, Lorenzo Federico (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2026)
The study of the neutrino-less double beta decay by heavy-ions double charge exchange (HI-DCE) represents a crucial step toward understanding the fundamental properties of neutrinos and the possible violation of lepton number conservation. Among the candidate isotopes for this rare process, plays a central role in current and next-generation experimental searches. In this work, I investigate the nuclear structure aspects relevant to the decay of through the analysis of the reaction at . The reaction dynamics were modeled using the coupled-channels code FRESCO using the Distorted Wave Born Approximation (DWBA), which allows for a detailed description of inelastic excitations and single-nucleon transfer processes that are sensitive to nuclear transition densities. Complementary large-scale shell-model calculations were carried out with KSHELL to obtain spectroscopic amplitudes and nuclear matrix elements for the relevant states. The theoretical results were directly compared with experimental differential cross sections from the NUMEN Collaboration, showing good overall agreement in both magnitude and shape. This comparison validates the reliability of the adopted reaction and structure models and provides important constraints on the nuclear structure components that dominate the nuclear matrix elements.